KONSEP HARTA PERSPEKTIF MAQASID AL-SYARIAH DAN IMPLEMENTASINYA PADA WAKAF TUNAI - Ariani Hidayat (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
Cash waqf is one of the instruments to empower the potential of public funds with the aim of alleviating poverty and other socio-economic problems. The substance of cash waqf is in line with the maqasid alshari'at which leads to al-maslahah al-mursalah (universal benefit) one of them is in order to realize social welfare through justice of income and wealth distribution. In addition, one of the implementation of maqasid al-syari'at contained in cash waqf is the principle ta'awun (mutual help) to the less fortunate.